TINGKAT PENGETAHUAN DAN PEMAHAMAN MASYARAKAT TENTANG PENGGUNAAN OBAT YANG BENAR DI KOTA KUPANG TAHUN 2014 - JEFRIN SAMBARA; NI NYOMAN YULIANI; YANTRI BURENI (JURNAL INFO KESEHATAN, 2014)
Medication is the primary requirement for being sick. When given the proper dosage can cure disease, relieve pain, and can improve human health. However, if not used appropriately and correctly will worsen the condition of patients with pain. Improper use of the drug can occur due to lack of knowledge and understanding of the correct use of medications. Therefore, the authors are interested in doing research with the title "The level of knowledge and understanding about the Community Right Use of Drugs in the city in 2014". This study aims to determine the level of knowledge and understanding of the correct use of drugs in the city in 2014. This research is a descriptive survey research. The study was conducted by analyzing primary data which can be directly from the public in the city of Kupang through questionnaires sheets according to the Guttman scale. The results showed that of the total 270 respondents surveyed, 48.52% know and understand about how to use the correct medications while 51.48% do not know and do not understand how to use the medicine properly.